Assessment of glucose profiles in routine diabetes care - Vogt, R.; Kohnert, K.-D.; Augstein, P.; Heinke, P.; Rackow, C.; Meyramov, G.G.; Vogt, L.; Salzsieder, E. (Fundamental and Experimental Biology, 2015)
The regular documentation of glucose measurements during insulin and / or oral drug therapy, meal intake, and special events in the daily life are crucial for doctors in the treatment of patients with diabetes mellitus. Therefore, we developed a method, which allows objective, rapid and comprehensive review of glucose pro-iles for the first time. On the basis of glucose values, either recorded by self-monitoring of blood glucose or by a continuous glucose monitoring with a sensor system, the Q-Score can easily be computed. Classification by Q-Score is simple, time-saving, and useful in terms of daily treatment routine. In addition, it involves analysis of the contribution of individual glycemic components expressed as the Q-Score and enables assessment of therapeutic efficacy. The method for determining the Q-Score, evaluation of glucose readings and self-control data as well as presentation of results and the therapeutic advancement will be implemented into the telemedicine information and communication system TeleDIAB®, which is available via world-wide.